Gaya hidup hedonisme pada mahasiswa: Adakah peranan kontrol diri dan Big Five Personality - Yusmita M; Suroso; Niken Titi Pratitis (INNER: Journal of Psychological Research, 2022)
Abstract Hedonic lifestyle affects many individuals in their late teens such as students, including students at the Makassar State University who often go to the mall, hang out in cafes, watch movies, and vacation with friends compared to campus activities or carrying out their obligations as students. One of the main causes of the emergence of a hedonic lifestyle is the individual’s personality and self-control. The subjects in this study were students of the Faculty of Economics, Makassar State University, with a total of 289 students as respondents. This research is quantitative research and analysis using the product-moment correlation test and Oneway Anova with the help of the SPSS 20 IMB for Windows program. The results of this study indicate that there is a negative relationship between the hedonistic lifestyle and self-control, which means that the higher the self-control that students have, the lower the hedonic lifestyle. The results of the Oneway Anova test between the hedonistic lifestyle and the Big Five Personality found that there were differences in the personality domain towards the hedonistic lifestyle. Furthermore, the results of this study found that individuals in the Neuroticism personality domain have a more hedonistic lifestyle, the Openness To Experience domain has a hedonistic lifestyle and the Extraversion Domain does not have a hedonistic lifestyle. Keywords: Hedonism lifestyle. Self-control. Big five personality